Comparing open-source DEM frameworks for simulations of common bulk processes - Dosta, Maksym; André, Damien; Angelidakis, Vasileios; Caulk, Robert; Celigueta, Miguel Ángel; Chareyre, Bruno; Dietiker, Jean-Franҫois; Girardot, Jérémie; Govender, Nicolin; Hubert, Cédric; Kobyłka, Rafal; Moura, Augusto Fontan; et al. (Computer Physics Communications, 2024)
Multiple software frameworks based on the Discrete Element Method (DEM) are available for simulating granular materials. All of them employ the same principles of explicit time integration, with each time step consisting of three main steps: contact detection, calculation of interactions, and integration of the equations of motion. However, there exist significant algorithmic differences, such as the choice of contact models, particle and wall shapes, and data analysis methods. Further differences can be observed in the practical implementation, including data structures, architecture, parallelization and domain decomposition techniques, user interaction, and the documentation of resources. This study compares, verifies, and benchmarks nine widely-used software frameworks. Only open-source packages were considered, as these are freely available and their underlying algorithms can be reviewed, edited, and tested. The benchmark consists of three common bulk processes: silo emptying, drum mixing, and particle impact. To keep it simple and comparable, only standard features were used, such as spherical particles and the Hertz-Mindlin model for dry contacts. Scripts for running the benchmarks in each software are provided as a datase
Keywords: Open source; Discrete Element Method; Benchmark